Screening candidate genes for fruit size based on QTL-seq in Chinese jujube - Pan, Yiling; Luo, Yujia; Bao, Jingkai; Wu, Cuiyun; Wang, Jiurui; Liu, Mengjun; Yan, Fenfen (Frontiers in Plant Science, 2024)
Fruit size is an important economic trait affecting jujube fruit quality, which has always been the focus of marker assisted breeding of jujube traits. However, despite a large number of studies have been carried out, the mechanism and key genes regulating jujube fruit size are mostly unknown. In this study, we used a new analysis method QTL-Seq (Bulked Segregant Analysis) to screen the parents 'Yuhong' and 'Jiaocheng 5' with significant phenotypic differences and mixed offspring group with extreme traits of large fruit and small fruit respectively, and then DNA mixed pool sequencing was carried out to further shortening the QTL candidate interval for fruit size trait, and excavated candidate genes for controlling fruit size. The candidate intervals related to jujube fruit size were mainly located on chromosomes 1, 5 and 10, and the frequency of chromosome 1 was the highest. Based on the QTL-seq results, the annotation results of ANNOVAR were extracted from 424 SNPs (Single Nucleotide Polymorphism) and 164 Indels (Insertion-deletion), from which 40 candidate genes were selected, and 37 annotated candidate genes were found in the jujube genome. Four genes (LOC107428904, LOC107415626, LOC125420708, and LOC107418290) that be associated with fruit size growth and development were identified by functional annotation of the genes in NCBI (National Center for Biotechnology Information). The genes can provide a basis for further exploration and identification on genes regulating jujube fruit size. In summary, the data obtained in this study revealed that QTL intervals and candidate genes for fruit size at the genomic level, which provides valuable resources for future functional studies and jujube breeding.